DEVELOPMENT TRENDS OF BLACKSMITH’S CRAFT BASED ON THE RESULTS OF THE INTERNATIONAL FESTIVAL “SVIATO KOVALIV” - Матоліч, І. Я. (Art and Design, 2020)
The article defines and outlines the processes of artistic blacksmithing revival in Ivano-Frankivsk based on the results of the annual International Festival “Sviato Kovaliv” (Blacksmith Festival). The attention is riveted on the analysis of artistic features of forged sculptural compositions that complement the urban environment, and their art history analysis has been carried out. Methodology. The methodological background is the principle of system approach and integrated research. The historical, comparative and art history methods have been used for the study of the selected object of research. Results. It has been established that one of the biggest in Eastern Europe is the International Blacksmith Festival “Sviato Kovaliv” in Ivano-Frankivsk which began its activities in 2003. The purpose of this event is the revival of blacksmithing traditions forgotten in Ukraine in the Soviet times and popularization of the artistic metal as a craft and an art. It has been defined that in the space of a few years the event has developed from the amateur level into the large-scale international project which nowadays includes a complex of events: public demonstration of blacksmithing, performances, competitions, international scientific conference, and art exhibition of blacksmithing. It has been established that one of the results of festival is the production of joint blacksmith’s works, which nowadays complement the urban environment of Ivano-Frankivsk, and their artistic features have been analysed. It has been found out that metal artworks can be both functional and decorative, often with a deep idea. The scientific novelty lies in the study of important aspect of the modern artistic blacksmithing revival in Ukraine using the example of the International Festival “Sviato Kovaliv” (Blacksmith Festival) in Ivano-Frankivsk. The attention is focused on the artistic features of forged chased work. Practical significance. The research allows broadening your knowledge about the artistic blacksmithing development in Ivano-Frankivsk that contributes to the attraction of obtained information in the study of modern blacksmithing in Halychyna (Galicia).